Analysis of risk in a commercial work of small porte in Imperatriz – MA - Jorge, Gustavo Pires do Nascimento (Brazilian Journal of Production Engineering, 2023)
Activities related to civil construction present numerous factors that can compromise the health and safety of workers who operate in it. The lack of training, low-skilled labor, heavy work routines, given the working conditions and inefficient inspection by the work management are some factors that contribute to the high accident rates in civil construction. The neglect and lack of importance given by entrepreneurs in this sector are worrying. The security offered to construction workers, most of the time, does not comply with safety standards. In this work, the application of FMEA in the civil construction environment in Imperatriz-MA in a small work was approached. Through interviews and the survey of photographic research on site, and from the data obtained, an analysis was carried out about the possibilities of using FMEA in works.